Career profile and pattern of racing for Thoroughbred jumps-racing horses in New Zealand - Gibson MJ; Legg KA; Gee EK; Chin YY; Rogers CW (CSIRO Publishing, 2024)
Context Racing structure and focus for racehorses differs across jurisdictions and is poorly described. In New Zealand and Australia, jumps racing accounts for a small proportion of total Thoroughbred races each year, as opposed to the larger jumps-racing (National Hunt) industry with purpose-bred horses found in the UK and Ireland. Aims This study aimed to describe the career profile and pattern of racing for Thoroughbred jumps-racing horses in New Zealand. Methods Metrics from every horse with a full jumps-racing career (n = 1276, 89% geldings) between the 2005/06 and 2021/22 racing seasons (n = 40,302 starts) were examined. Descriptive statistics, box plots and heat maps were used to describe the data, by using horse age as a proxy for career progression. Key results Jumps-racing horses had a median of 17 flat starts (IQR 9–30) before their first jumps-racing start. The median career of a jumps-racing horse was 3.7 years (IQR 2.3–5.2) and 29 starts (IQR 16–44). Older horses had a decreasing number of flat-racing starts and an increasing proportion of steeplechase-racing starts. However, the majority of horses still had at least one flat-race start per calendar year, often prior to the first jumps race. Most horses had one spell each season (length 194 days, IQR 124–259), and a condensed preparation length over the winter months, with a median of 14 days (IQR 10–21) between starts. Conclusion The career pattern for jumps-racing horses in New Zealand reflects the industry retention of horses with a prior career in flat racing into a secondary jumps-racing career. Successful horses have increased focus on preparation for the winter jumps-racing season. Implications Jumps racing provides a secondary racing career for some flat-racing horses, particularly geldings. This strategy reduces wastage of horses from the industry.
Keywords: hurdle; jumps racing; periodicity; secondary career; steeplechase; sustainability; Thoroughbred racing; wastage